The Relation Between Nutritional Status and Menstrual Cycles in Young Women at the Tenth Grade of SMA PGRI 4 Denpasar - Ni Kadek Wira Adnyani (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2013)
Nutritional status is the state of human body caused by the consumption, absorption and use of nutrients. Poor nutrition in young women can affect sexual maturation, growth, organ function and reproductive function will be disturbed. The disruption of reproductive function will impact on menstrual disorders. This research aims to determine the relation between nutritional status and menstrual cycles in young women at the Tenth Grade of SMA PGRI 4 Denpasar. This research is a descriptive correlation with cross-sectional approachment and has involved 72 respondents that selected by purposive sampling. The results are 40,3% young women with undernutrition, 52,8% young women with eunutritional state and 6,9% young women with overnutritional state. The regular menstrual cycles are 61,1% teenagers and the irregular menstrual cycles are 38,9% teenagers. Based on research results with coefficient-contingency test (p<0,05), obtained p=0,000 and it means there is a significant relation between nutritional status and menstrual cycles in young women at the tenth grade of SMA PGRI 4 Denpasar. The result of advised for school for back turn activities school health efforts, where one of the program is all about balanced nutrition in young women.